KOMITMEN ORGANISASIONAL, KEPUASAN KOMPENSASI, KEPUASAN PEKERJAAN, DAN KINERJA KEUANGAN RETAIL MODERN - R. Philipus Lewis (Jurnal Riset Akuntansi dan Keuangan, 2013)
The purpose of this study is to examine the effect of organizational commitment, job satisfatction, pay satisfation on modern retail busines’ financial performance. Primary data have been collected from 54 modern retail’s employees. Multiple regression is used for testing three hypotheses. The results show that organizational commitment has effect on modern retail busines’ financial performance. Meanwhile, job satisfatction and pay satisfation have not influance on modern retail busines’ financial performance. Keywords: organizational commitment, pay satisfaction, job satisfacion, financial performance